Assessment of survival and cardiotoxicity of adjuvant trastuzumab among HER2 breast cancer patients in an oncology centre in Malaysia / Harissa H Hasbullah … [et al.] - Hasbullah, Harissa H; Bustamam, Anita; Tho, Lye Munn; Phua, Vincent (Universiti Teknologi MARA Cawangan Selangor, 2018)
Adjuvant trastuzumab has been used in human epidermal growth factor-2 (HER2) breast cancer to improve survival but with concern of cardiotoxicity. Our study is the first to review efficacy and toxicity of adjuvant trastuzumab in Malaysia. Methods: This is a retrospective cohort study on HER2 non metastatic breast cancer patients in University Malaya Medical Centre diagnosed between October 2006 and May 2011. Two cohorts were created based on whether or not they received adjuvant trastuzumab. Disease free survival (DFS) and overall survival (OS) for both groups were estimated using Kaplan Meier method and compared using Log rank test. Cox proportional hazards regression models analysed for potential covariates of age, tumour size and grade, node and estrogen receptor (ER) status. Trastuzumab cardiotoxicity was defined as left ventricular systolic dysfunction or heart failure with or without symptoms and graded using Common Terminology Criteria for Adverse Events (CTCAE 4.0). Results: 170 HER2 non metastatic breast cancer patients were identified. Thirty-three received trastuzumab and 136 did not. Median age was 53.4 ± 10.3 years old. Significantly more ER negative patients received trastuzumab. Four years DFS in ‘trastuzumab’ versus ‘no trastuzumab’ cohort was 90.9% vs 74.5% (p = 0.027). Four years OS was 91% vs 84.7% (p = 0.30) respectively. Majority tolerated trastuzumab with no toxicity. Five patients (15.2%) experienced cardiotoxicity (all grade I).Conclusions: Adjuvant trastuzumab significantly improved DFS in HER2 breast cancer. Treatment was well tolerated. With this we propose the justification for adjuvant trastuzumab in HER2 breast cancer in our population.